2003
DOI: 10.1115/1.1574822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unsteady Stator Wake—Rotor Double-Leakage Tip Clearance Flow Interaction on Time-Average Compressor Performance

Abstract: A study has been conducted, using unsteady three-dimensional Reynolds-averaged Navier-Stokes simulations to determine the impact on rotor performance of the interaction between upstream (steady defect and time-varying defect) stator wakes and rotor tip clearance flow. The key effects of the interaction between steady stator wakes and rotor tip clearance flow are: 1) a decrease in loss and blockage associated with tip clearance flow; 2) an increase in passage static pressure rise. Performance benefit is seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In Figure 7, clear cut lines of the relative velocity contour demarcating the higher flow reversal regions from the main flow can be observed. It is seen that for this UNS rotor case at φ = 0.50 and τ/ch = 2.7%, where the leakage vortex penetration and blockage are the highest among the various clearance and rotor configurations, the relative velocity deficit region is observed to penetrate close to the TE of the adjacent blade, without crossing the tip again to cause what is referred to as "double leakage" [10]. Double leakage refers to tip clearance flow leaking across the adjacent blade tip again but with a lower streamwise velocity component.…”
Section: Tip Leakage Phenomenamentioning
confidence: 84%
“…In Figure 7, clear cut lines of the relative velocity contour demarcating the higher flow reversal regions from the main flow can be observed. It is seen that for this UNS rotor case at φ = 0.50 and τ/ch = 2.7%, where the leakage vortex penetration and blockage are the highest among the various clearance and rotor configurations, the relative velocity deficit region is observed to penetrate close to the TE of the adjacent blade, without crossing the tip again to cause what is referred to as "double leakage" [10]. Double leakage refers to tip clearance flow leaking across the adjacent blade tip again but with a lower streamwise velocity component.…”
Section: Tip Leakage Phenomenamentioning
confidence: 84%
“…Khalid stated that this reduction of total pressure in tip leakage flow changes the leakage flow angle and thus leads to variation in endwall blockage. Sirakov 32 also proved the assumption of Storer and Cumpsty in the original model that On the other hand, the static pressure distribution on the suction side of blade tip is very different from the static pressure well away from the endwall, and is affected by the leakage vortex (TLV) 8 and the shockinduced boundary layer separation (SIBLS). 33 Although previous studies 3,8 have revealed that the clearance jet flow has the same static pressure as blade suction surface at blade tip, the effects of static pressure distribution at blade tip suction side on tip clearance loss have seldom been investigated.…”
Section: Estimation Of Blade Tip Loading Distributionmentioning
confidence: 94%
“…It seems that the mixing-plane assumption at the interfaces between the rotating and stationary domains causes this discrepancy. The beneficial effects of blade row interaction on rotor performance were studied by Valkov and Tan [12], Sirakov and Tan [13], and Graf et al [14]. Valkov and Tan [12] showed that the upstream wake recovery increased the pressure rise in the downstream passage by 1 to 3%.…”
Section: Calculation Models and Methodsmentioning
confidence: 99%
“…Valkov and Tan [12] showed that the upstream wake recovery increased the pressure rise in the downstream passage by 1 to 3%. Sirakov and Tan [13] explained that the upstream wake suppressed double leakage of the tip clearance flow, thereby enhancing the pressure rise by about 2%. The effects of the downstream stator on the rotor are shown in Graf et al [14].…”
Section: Calculation Models and Methodsmentioning
confidence: 99%